The Influence of Vertical Housing Development on the Spatial Structure in Medan Petisah District - khoirina, nabilah (Talenta Publisher, 2025)
Residential land is becoming less available as Medan city centers continue to grow. As a result, land and house values have skyrocketed. In addition, the increasing number of city dwellers has made it more difficult to supply the demand for housing. One way to solve this problem is to build vertikal buildings that provide vertikal hunian that can satisfy the needs of the local populace. Perimahan vertikal may be a necessary and practical measure for the general public who wish to interact with workplaces, public spaces, educational institutions, and other activities.Vertical buildings are buildings that have a perpendicular shape and arrangement from bottom to top. Low-rise buildings have three or four layers of floors or a height of + 10 meters, while high-rise buildings have more than four layers of floors and a height of more than 10 meters. Vertical buildings or multi-storey buildings have several influences, including land efficiency. Vertical use of space can increase land efficiency. House prices. Demand for space. Multi-storey buildings are built to meet the high demand for space in the area. Multi-storey buildings are built because of limited expensive land in urban areas.The demand for apartments becomes a wise investment when the population of urban areas continues to expand but there is a lack of equivalent urban land for housing. With its large capacity, vertical housing may produce green open space in a vertical setting.